2019
DOI: 10.1111/pde.13954
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric trichotillomania: Review of management

Abstract: Trichotillomania can present in childhood, with many families seeking initial evaluation by a dermatologist for hair loss. Prompt and accurate diagnosis by dermatologists is crucial, as children can suffer from academic or social impairments as well as mental health sequelae. Children are especially vulnerable to lasting psychological distress from appearance‐related bullying. This article reviews the psychosocial impacts of pediatric trichotillomania and the current interventions studied in this population. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…Previous text has suggested that patients initially pre­sent for hair loss at dermatology [9]. However, most of our patients were treated by behavioral health at initial presentation (63.5%).…”
Section: Discussion/conclusionmentioning
confidence: 85%
See 3 more Smart Citations
“…Previous text has suggested that patients initially pre­sent for hair loss at dermatology [9]. However, most of our patients were treated by behavioral health at initial presentation (63.5%).…”
Section: Discussion/conclusionmentioning
confidence: 85%
“…In fact, 12 patients treated in a psychodermatology service for various skin disorders noted improvement in their conditions [20]. Since habit reversal therapy is the most effective therapeutic option to date, dermatologists are recommended to create partnerships with experienced community mental health providers [9].…”
Section: Discussion/conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Diagnosing scalp trichotillomania in pediatric patients is often tough as other disorders have similar clinical presentation, mainly alopecia areata and tinea capitis [1, 10]. Two types of hairpulling have been described for trichotillomania: automatic and focused [3, 5]. Automatic occurs outside of one’s own awareness, while focused pulling happens in awareness and in response to negative emotional states, such as stress, sadness, anger, or anxiety [3, 5, 8].…”
Section: Discussion/conclusionmentioning
confidence: 99%